2022
DOI: 10.3390/microorganisms10020242
|View full text |Cite
|
Sign up to set email alerts
|

Torque Teno Sus Virus (TTSuV) Prevalence in Wild Fauna of Northern Italy

Abstract: Torque teno sus virus (TTSuV) is a non-enveloped circular ssDNA virus which frequently infects swine and has been associated with hepatic, respiratory, and autoimmune disorders. TTSuV’s pathogenic role is still uncertain, and clear data in the literature on virus reservoirs are lacking. The aims of this study were to investigate the presence of potentially zoonotic TTSuV in wild animals in Northern Italy and to evaluate their role as reservoirs. Liver samples were collected between 2016 and 2020 during four hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Phylogenetic analysis indicated that all TTSuV strains detected in Tibetan pigs belong to TTSuV2 and could be further divided into TTSuV2a and TTSuV2b sub-genotypes. Previous studies have shown that TTSuV can serve as an enhancing factor of co-infection with porcine circovirus and respiratory disease viruses, particularly PCV2 [7,33,34]. In this study, the TTSuV in Tibetan pigs showed the same positive rate as PCV2 (22.8%), and among PCV2-positive samples, the proportion of PCV2/TTSuV2 co-infection was as high as 65.2% (15/23), suggesting it is likely the main cause of PRDC in Tibetan pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis indicated that all TTSuV strains detected in Tibetan pigs belong to TTSuV2 and could be further divided into TTSuV2a and TTSuV2b sub-genotypes. Previous studies have shown that TTSuV can serve as an enhancing factor of co-infection with porcine circovirus and respiratory disease viruses, particularly PCV2 [7,33,34]. In this study, the TTSuV in Tibetan pigs showed the same positive rate as PCV2 (22.8%), and among PCV2-positive samples, the proportion of PCV2/TTSuV2 co-infection was as high as 65.2% (15/23), suggesting it is likely the main cause of PRDC in Tibetan pigs.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the role of TTSuV as a commonly distributed pathogen such as in the investigated Swiss pigs was also emphasized by the detection of TTSuV1 and one in several cell lineages (also one frozen cell culture from 1985) [ 41 ] which was interpreted as contamination. Different wildlife species, positive for TTSuV1 or TTSuV2ka, may play a role as reservoirs [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…TSuV1 and TTSuVk2a have been detected in pig populations worldwide with frequencies of infection ranging from 24 to 100% [79][80][81][82][83][84][85][86], while very little data are reported in wild boars worldwide [72,74,82,87,88].…”
Section: Torque Teno Sus Virus (Ttsuv)mentioning
confidence: 99%